The embryology, seed coat, and conservation of some Kenyan species of the orchidaceae - Ochora, John (University of Cape Town, 2014)
Summary in English. === Bibliography: p. 165-198. === Aspects of embryology, seed morphological features and symbiotic seed germination of the Kenyan orchid species of the subfamily Epidendroideae were examined critically in order to elucidate their development and importance in conservation. The embryology of ca. 70 species was studied by clearing-squash techniques and differential-interference-contrast optics and seeds of ca. 50 species were studied by scanning electron microscopy to determine their variations.